Developmental training model for the sport specialized youth athlete: A dynamic strategy for individualizing load-response during maturation - Jayanthi, N.; Schley, S.; Cumming, S. P.; Myer, G. D.; Saffel, H.; Hartwig, T.; Gabbett, T. J. (Sports Health: A Multidisciplinary Approach, 2022)
Context: Most available data on athletic development training models focus on adult or professional athletes, where increasing workload capacity and performance is a primary goal. Development pathways in youth athletes generally emphasize multisport participation rather than sport specialization to optimize motor skill acquisition and to minimize injury risk. Other models emphasize the need for accumulation of sport- and skill-specific hours to develop elite-level status. Despite recommendations against sport specialization, many youth athletes still specialize and need guidance on training and competition. Medical and sport professionals also recommend progressive, gradual increases in workloads to enhance resilience to the demands of high-level competition. There is no accepted model of risk stratification and return to play for training a specialized youth athlete through periods of injury and maturation. In this review, we present individualized training models for specialized youth athletes that (1) prioritize performance for healthy, resilient youth athletes and (2) are adaptable through vulnerable maturational periods and injury. Evidence Acquisition: Nonsystematic review with critical appraisal of existing literature. Study Design: Clinical review. Level of Evidence: Level 4. Results: A number of factors must be considered when developing training programs for young athletes: (1) the effect of sport specialization on athlete development and injury, (2) biological maturation, (3) motor and coordination deficits in specialized youth athletes, and (4) workload progressions and response to load. Conclusion: Load-sensitive athletes with multiple risk factors may need medical evaluation, frequent monitoring, and a program designed to restore local tissue and sport-specific capacity. Load-naive athletes, who are often skeletally immature, will likely benefit from serial monitoring and should train and compete with caution, while load-tolerant athletes may only need occasional monitoring and progress to optimum loads. Strength of Recommendation Taxonomy (SORT): B.